2023
DOI: 10.1111/jcpe.13850
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evidence of different surgical techniques for the management of vertical alveolar ridge defects in terms of complications and efficacy: A systematic review and network meta‐analysis

Abstract: AimTo systematically appraise the available evidence on vertical ridge augmentation (VRA) techniques and estimate a treatment‐based ranking on the incidence of complications as well as their clinical effectiveness.Materials and MethodsSearches were conducted in six databases to identify randomized clinical trials comparing VRA techniques up to November 2022. The incidence of complications (primary) and of early, major, surgical and intra‐operative complications, vertical bone gain (VBG), marginal bone loss, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Indeed, when large vertical alveolar ridge defects are present, bone grafting techniques seem to have a higher incidence of complications. Alotaibi et al [22] performed a network meta-analysis to compare the results associated with the use of onlay and inlay grafts, several types of membranes (resorbable and nonresorbable), distraction osteogenesis, tissue expansion, and short implants. These authors concluded that all grafting options (except the use of resorbable membranes) were associated with a statistically significant higher odds ratio of complications [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, when large vertical alveolar ridge defects are present, bone grafting techniques seem to have a higher incidence of complications. Alotaibi et al [22] performed a network meta-analysis to compare the results associated with the use of onlay and inlay grafts, several types of membranes (resorbable and nonresorbable), distraction osteogenesis, tissue expansion, and short implants. These authors concluded that all grafting options (except the use of resorbable membranes) were associated with a statistically significant higher odds ratio of complications [22].…”
Section: Discussionmentioning
confidence: 99%
“…Alotaibi et al [22] performed a network meta-analysis to compare the results associated with the use of onlay and inlay grafts, several types of membranes (resorbable and nonresorbable), distraction osteogenesis, tissue expansion, and short implants. These authors concluded that all grafting options (except the use of resorbable membranes) were associated with a statistically significant higher odds ratio of complications [22]. It is also important to stress that when extraoral bone harvesting is required, patients might experience pain in the donor site area and gait and sensory disturbances if the iliac crest is involved [23].…”
Section: Discussionmentioning
confidence: 99%
“…Non-resorbable membranes demonstrate good mechanical properties, enabling them to retain their shape and provide space for new tissue formation [ 62 ], thus allowing for precise control over their barrier function [ 11 ]. A systematic review concerning vertical bone gain revealed that GTR techniques using non-resorbable membranes yield the most favorable results [ 63 ]. However, it is subject to certain limitations.…”
Section: Classification Of Current Bone Repair Materialsmentioning
confidence: 99%
“…To enhance dental implant therapy by reconstructing deficient alveolar ridges, various bone regenerative techniques have been assessed (9)(10)(11)(12)(13). Guided bone regeneration (GBR) is one such technique, which involves a membrane application to prevent non-osteogenic tissues interference in bone regeneration, closely mimicking the natural osteogenesis process (14).…”
Section: Introductionmentioning
confidence: 99%